HISTORISITAS DAN PERAN PONDOK PESANTREN SOMALANGU DI PESISIR SELATAN - Atabik Atabik (IBDA` : Jurnal Kajian Islam dan Budaya, 2014)
This paper reveals the Somalangu Islamic boarding school in Kebumen that has an important role for the people in southern coast of Java. Historically, the existence of the school becomes the starting point of Islam development there. In social transformation, the school fought against colonizer. Unfortunately the school was considered deviant when there was a conflict with the national army. Islamic force (AOI) that was led by KH Mshfudz Abdurrahman was accused to build an Islamic country and the misunderstanding made him killed. Meanwhile, KH Mahfudz Abdurrahman only wanted to fight against colonizer.